Comparison of early osseointegration of non-thermal atmospheric plasma-functionalized/ SLActive titanium implant surfaces in beagle dogs - Long, Li; Zhang, Min; Gan, Shuaiqi; Zheng, Zheng; He, Yanjin; Xu, Jia; Fu, Ruijie; Guo, Qiang; Yu, Deping; Chen, Wenchuan (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The hydrophilic dental implants are gaining increasing interest for their ability to accelerate the bone formation. However, commercially available hydrophilic implants, such as SLActive™ have some major limitations due to their time-dependent biological aging and less cost effectiveness. Even though, non-thermal atmosphere plasma (NTAP) treatment is a reliable way to gain hydrophilic surface and enhance osseointegration. However, a few studies have been done to compare osseointegration of NTAP functionalized titanium implant and commercially available hydrophilic implants. Purpose: In this study, we compare the osseointegration abilities of NTAP functionalized titanium implant and Straumann SLActive○R. Material and methods: The NTAP effectiveness was examined using in vitro cell experiments. Then, six beagle dogs were included in vivo experiment. Straumann SLActive implant, SLA implants and SLA implants treated with NTAP were implanted in mandibular premolar area of dogs. After 2w, 4w and 8w, the animals were sacrificed and specimens were collected. Radiographic and histological analysis were used to measure osseointegration. Results: NTAP treatment accelerated the initial attachment and differentiation of MC3T3-E1cell. In vivo, bone parameters (e.g. BIC value, BV/TV etc) and volume of new bone of NTAP groups was close to that of SLActive group. Additionally, although there was no statistical difference, osseointegration of SLActive and NTAP groups were obviously superior to that of SLA group. Conclusions: NTAP-functionalized implant enhanced cell interaction with material and subsequent bone formation. The osseointegration of NTAP-functionalized implant was comparable to that of SLActive implant at early osseointegration stage.